Partnering with healthcare: The experiences of consumer representatives - Corey Adams; Anthony Brown (The Beryl Institute, 2023)
The importance of consumer advocacy in person-centred healthcare service planning and delivery is growing. In Australia, the role of the "Consumer Representative" (known internationally as "Patient and Family Advisors") is to advocate for patients and their families' needs to improve service planning, healthcare design, and service evaluation. As the role of consumer representatives evolves and matures within the healthcare setting, it is crucial to comprehend their experiences and identify key insights to support and enhance their role within healthcare organizations. To achieve this, a focus group of four Consumer Representatives was conducted and their views were compiled into a single commentary. Our findings suggest that Consumers Representatives are driven by a desire to assist others, but they may feel dissatisfied if their role is perceived as tokenistic or lacks meaningful engagement. Consumer Representatives suggested various ways to improve consumer participation, including role clarification, meeting facilitation, and the development of supportive consumer networks. Experience Framework This article is associated with the Patient, Family & Community Engagement lens of The Beryl Institute Experience Framework (https://www.theberylinstitute.org/ExperienceFramework). <a href="https://www.theberylinstitute.org/page/PXSEARCH#resource-list-all/?view_28_page=1&view_28_filters=%5B%7B%22field%22%3A%22field_38%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22PXJ%20Article%22%5D%7D%2C%7B%22field%22%3A%22field_40%22%2C%22operator%22%3A%22in%22%2C%22value%22%3A%5B%22Patient%2C%20Family%20%26%20Community%20Engagement%22%5D%7D%5D">Access other PXJ articles related to this lens. Access other resources related to this lens.